Effect of Nickel Supplementation on Growth, Haematology, Biomarkers of Energy and Protein Metabolism of Heifers Fed Urea Based Diet - Rashmi Singh; Kumar, Vinod; Muneendra Kumar; Raju Kushwaha; Avinash Kumar; Ankita Patel (Indian Journal of Animal Nutrition, 2023)
This study was conducted to assess the effect of nickel (Ni) supplemental effect on nutrient intake, digestibility, haematology and blood biochemical in growing cattle. Eighteen Sahiwal heifers were randomly assigned to three groups for 90 days. Control group were fed on basal diet without nickel and urea whereas, animals in treatment group-1 (T1) was supplemented concentrate with urea (3%) without Ni and treatment group-2 (T2) animals were supplemented with 5.0 mg Ni/kg DM/animal and concentrate containing urea (3%). The nutrient requirements of heifers were met by feeding concentrate mixture, berseem and wheat straw as per NRC (2001) guideline. Adding 5.0 mg Ni/kg DM to the diet of growing heifers had no effect on DMI, body weight gain, FCR, FCE in heifer fed urea based diet. No effects of treatments were observed on haemoglobin concentration, haematocrit value, biomarkers of lipid and protein metabolism i.e. plasma triacylglycerol, cholesterol, plasma total protein, plasma albumin and plasma globulin. The plasma glucose level was found significantly higher (P